Unraveling rare form of adult-onset NIID by characteristic brain MRI features: A single-center retrospective review - Li, Fan; Wang, Qi; Zhu, Ying; Xiao, Jiangxi; Gu, Muliang; Yu, Jiaxi; Deng, Jianwen; Sun, Wei; Wang, Zhaoxia (Frontiers in Neurology, 2022)
Adult-onset neuronal intranuclear inclusion disease (NIID) is a rare neurodegenerative disorder with high clinical heterogeneity. Previous studies indicated that the high-intensity signals in the corticomedullary junction on diffusion-weighted imaging (DWI) on brain MRI, known as the “ribbon sign,” could serve as a strong diagnostic clue. Here we used the explorative approach to study the undiagnosed rate of adult-onset NIID in a single center in China via searching for the ribbon sign in picture archive and communication system (PACS) and report the clinical and radiological features of initially undiagnosed NIID patients. Consecutive brain MRI of 21,563 adult individuals (≥18 years) in the PACS database in 2019 from a tertiary hospital were reviewed. Of them, 4,130 were screened out using the keywords “leukoencephalopathy” and “white matter demyelination.” Next, all 4,130 images were read by four neurologists. The images with the suspected ribbon sign were reanalyzed by two neuroradiologists. Those with the ribbon sign but without previously diagnosed NIID were invited for skin biopsy and/or genetic testing for diagnostic confirmation. The clinical features of all NIID patients were retrospectively reviewed. Five patients with high-intensity in the corticomedullary junction on DWI were enrolled. Three patients were previously diagnosed with NIID confirmed by genetic or pathological findings and presented with episodic encephalopathy or cognitive impairment. The other two patients were initially diagnosed with limb-girdle muscular dystrophy (LGMD) with rimmed vacuoles (RVs) and normal pressure hydrocephalus (NPH) in one each. Genetic analysis demonstrated GGC repeat expansion in the NOTCH2NLC gene of both, and skin biopsy of the first patient showed the presence of intranuclear hyaline inclusion bodies. Thus, five of the 21,563 adult patients (≥18 years) were diagnosed with NIID. The distinctive subcortical high-intensity signal on DWI was distributed extensively throughout the lobes, corpus callosum, basal ganglia, and brainstem. In addition, T2-weighted imaging revealed white matter hyperintensity of Fazekas grade 2 or 3, atrophy, and ventricular dilation. Distinctive DWI hyperintensity in the junction between the gray and white matter can help identify atypical NIID cases. Our findings highly suggest that neurologists and radiologists should recognize the characteristic neuroimaging pattern of NIID.